Passenger strand loading in overexpression experiments using microRNA mimics - Søkilde, Rolf (RNA Biol, 2015)
MicroRNAs (miRNAs) are important regulators of gene function and manipulation of miRNAs is a central component of basic research. Modulation of gene expression by miRNA gain-of-function can be based on different approaches including transfection with miRNA mimics; artificial, chemically modified miRNA-like small RNAs. These molecules are intended to mimic the function of a miRNA guide strand while bypassing the maturation steps of endogenous miRNAs. Due to easy accessibility through commercial providers this approach has gained popularity, and accuracy is often assumed without prior independent testing. Our in silico analysis of over-represented sequence motifs in microarray expression data and sequencing of AGO-associated small RNAs indicate, however, that miRNA mimics may be associated with considerable side-effects due to the unwanted activity of the miRNA mimic complementary strand.